Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
[tex]x^2-11x+14=0 \\ \\
a=1 \\ b=-11 \\ c=14 \\ b^2-4ac=(-11)^2-4 \times 1 \times 14=121-56=65 \\
x=\frac{-b \pm \sqrt{b^2-4ac}}{2a}=\frac{-(-11) \pm \sqrt{65}}{2 \times 1}=\frac{11 \pm \sqrt{65}}{2} \\
\boxed{x=\frac{11 - \sqrt{65}}{2} \hbox{ or } x=\frac{11+\sqrt{65}}{2}}[/tex]
x² - 11x + 14 = 0
x = -(-11) +/- √((-11)² - 4(1)(14))
2(1)
x = 11 +/- √(121 - 56)
2
x = 11 +/- √(65)
2
x = 11 +/- 8.062257748
2
x = 11 + 8.062257748 x = 11 - 8.062257748
2 2
x = 19.062257748 x = 2.937742252
2 2
x = 1.906225775 x = 1.468871126
x = -(-11) +/- √((-11)² - 4(1)(14))
2(1)
x = 11 +/- √(121 - 56)
2
x = 11 +/- √(65)
2
x = 11 +/- 8.062257748
2
x = 11 + 8.062257748 x = 11 - 8.062257748
2 2
x = 19.062257748 x = 2.937742252
2 2
x = 1.906225775 x = 1.468871126
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.